Social Costs of Direct and Indirect Land Use by Transport Infrastructure: An Estimation for The Netherlands - Bruinsma, Frank; Mark Koetse, Mark; Rietveld, Piet; Vreeker, Ron (European Journal of Transport and Infrastructure Research, 2002)
In this paper the social costs of land use for transport infrastructure are investigated for the Netherlands. We pay attention to the acquisition costs of land for infrastructure and the indirect costs of land use caused by transport. The paper gives an overview of the problems associated with measuring land related costs of transport infrastructure. Estimates are given of land use (in m2) for various types of transport infrastructure. In addition some of the land related cost categories are estimated. These costs are allocated to the various transport modes (cars and trucks of various types, barges, rail, and aircraft) on the basis of their relative transport kilometres and their passenger car equivalents. We find that direct and indirect land use equals respectively 7.2% and 1.6% of the total area of the Netherlands. Indirect land use appears to be especially important for aviation. The importance of indirect land use is shown by the value of land involved. The economic valuation of the indirect land use is about 16% of the total land related costs of transport infrastructure.